Behavioral Architecture Approach to Concept of Housing for the Face of Pandemic - Zhilli Izzadati Khairuni; Kemala Jeumpa (Talenta Publisher, 2021)
One effect caused by a calamity is the psychological impact on the community. In December 2019 covid-19 viral infected many countries including Indonesia which later changed his status to make cause serious problems because there is no vaccine to prevent transmission of the virus. This condition requires every society to comply with government regulations as quarantine, PSBB, WFH, social distancing. The psychological impact that is often found in society is afraid of panic and other stress. Psychology is closely related to conducting this study will discuss architectural behavior that plays a role in the relationship between people and space. This research as if would explain what occurred in behavior and how your family made the architect can solve this problem by emphasizing psychiatric problems through the application for building design, occupancy of a room. The theory of architecture as a guide in determining objects for the attention that the occupants need through analysis of the type of activity and used before and during the pandemic. This approach asserts the need to understand the behavior and needs of the people living in the house in use. This research activity was carried out with space objects selected based on the similarity of form and design of the average home in Medan City. In activities, the research was conducted with a sample housing path in our name in “Villa Nusa Sempurna” with different types of houses, and various characters users and primary focus will also be on the type of house that is most in demand are in residential. Is a type of type 70 most interested in shape and arrangement with the most commonly found in residential of the town. The result of this research is designed products have been analyzed based on the assessment of behavior so that it can become a new alternative designing safe and comfortable housing for the face of a pandemic.